Ferroptosis: a new perspective on the pathogenesis of radiation-induced cataracts - Yufu Tang; Hongying Liang; Lixia Su; Xiangming Xue; Jingming Zhan (Frontiers Media S.A., 2024)
Ionizing radiation is a significant risk factor for cataracts, but the pathogenesis of radiation-induced cataracts remains incompletely understood. Ferroptosis, an iron-dependent form of programmed cell death discovered in recent years, has gained increasing attention for its role in various diseases. This article systematically reviews research progress on ionizing radiation, ferroptosis, age-related cataracts, and radiation-induced cataracts. It proposes the "ferroptosis hypothesis" for the pathogenesis of radiation-induced cataracts. Through ionization and oxidative stress effects, ionizing radiation leads to elevated free iron levels and exacerbated lipid peroxidation in lens cells, activating the ferroptosis pathway and resulting in lens opacity. The involvement of ferroptosis in the development of age-related cataracts suggests that it may also be an important pathogenic mechanism of radiation-induced cataracts. Targeting the ferroptosis pathway may be a novel strategy for preventing and treating radiation-induced cataracts. Furthermore, developing new ferroptosis-specific inhibitors with improved targeting and pharmacokinetic properties is also an essential direction for research on preventing and treating radiation-induced cataracts. The study of ferroptosis provides new insights into the mechanism and management of radiation-induced cataracts, potentially transforming radiation-induced cataracts from "inevitable" to "preventable and treatable."